Implementasi Sistem Pemantauan Kelayakan Kapal Pada Proses Pengujian Kapal Menggunakan Teknologi Internet of Things - Pristovani, Dimas; Abu Jami’in, Muhammad; Singgih Setiyoko, Annas; Toto Wibowo, Alvalo; Leonard, Rikky (The Indonesian Journal of Computer Science, 2024)
A new ship must doing a sea trial inspection before handover to the owner based on International Maritime Organization regulation under Resolution MSC.137. Currently, these inspections are conducted manually. So, the Ship Qualification and Clasification System using Internet of Things (IoT) technology are highly needed. This system made up of hardware connected to an Android application and a web-based application that monitors real-time data on position, speed, inclination, wind speed, and time. Data logger are performed simultaneously on the hardware, Android app, and web-based app, creating redundancy in data logging. In practice, The results of these trials ensure that the ship's technical specifications comply with agreed standards, as well as strengthening the confidence of all parties involved in the testing project. With this success, an IoT-based monitoring and analysis system can be a reliable solution for operational needs and evaluating ship performance